Divine tides [compact disc] - Copeland, Stewart; Copeland, Stewart; Kej, Ricky, 1981- (Ponderosa Music Records SRL, 2021)
"Divine Tides by Stewart Copeland and Ricky Kej features artists from all over the world. Soundscapes and melodies meet pulsating rhythms amidst lush ambient textures, which elevate the senses into a realm of spiritual solitude, where the soul is free"--Container.